Characterization of saline dust emission resulted from Urmia Lake drying. Issue 1 (December 2015) - Gholampour, Akbar; Nabizadeh, Ramin; Hassanvand, Mohammad; Taghipour, Hasan; Nazmara, Shahrokh; Mahvi, Amir
Abstract Compared with common dust storms, saline dust storms transport high concentrations of fine-grain saline and alkaline material. The saline dust storm differs from common dust storm, especially considering the sources of the suspended particulate matter (PM), chemical composition, grain size, and circulation processes. Atmospheric particulate matters (TSP, PM10, PM2.5, and PM1 ) and their water-soluble ions were concurrently measured at two sites located at north and southeast part of Urmia lake from January 2013 to September 2013. Particulate matters (PMs) were measured using high volume sampler and HAZ-DUST EPAM-5000 particulate air monitors. In both of the sampling sites, the highest concentration of PM was observed during the summer season (521.6, 329.1, 42.6, and 36.5 for TSP, PM10, PM2.5, and PM1, respectively). A total of 11 inorganic water-soluble ions in the TSP and PM10 were identified by ion chromatography (IC). No statistically significant difference was found between PM's ions concentrations of two sampling sites. The average of the total measured water-soluble ions in the sampling sites was 28.75 ± 12.9 μg/m3 (11.9 ± 4.8% of total TSP mass) for TSP and 14.65 ± 7.1μg/m3 (8.7 ± 4.4 of total PM10 mass) for PM10 . Among all detected ions, sulfate was the dominant constituent followed by nitrate and sodium. This study showed that the water soluble salts compose 3–20% of the total mass of TSP and PM10 . The PCA analysis showed that saline particulates formed from Urmia lake bed were the dominant source (57.6 %) of TSP. In addition, saline particulates together with crustal materials resulted from resuspension were the main source (59.9%) of PM10 .